The Prevalence of migraine and associated factors among medical students in Ouagadougou (Burkina Faso) - Dabilgou, Alfred Anselme; Dravé , Alassane; Kyelem , Julie Marie Adeline Wendlamita; Doukouré , Mahamoudou Lamine; Napon , Christian; Millogo , Athanase; Karfo , Kapouné; Kaboré , Jean (Headache Medicine, 2023)
Objective: To determine the prevalence, clinical characteristics and impact of migraine among medical students in the city of Ouagadougou. Methods: This across-sectional study was carried out during a period of 6 months from August 2021 to January 2022. Participants were selected by stratified random sampling according to academic level. Hetero-administered questionnaire was administred to each student. Migraine was diagnosed according to the ICHD 3rd edition criteria and the MIDAS was used to assess the impact of migraine on students' quality of life. Results: Two hundred and twenty seven students were selected for this study. The prevalence of migraineurs was 31.8%. Their mean age was 22.20±2.67 years. There was female predominance among the migraineurs (73.9%). More than half of the migraineurs had a family history of headache disorders (53.6%). Migraine without aura was the most frequent subtype (59.4%). Visual aura was predominant (78.2%). Migraine was of moderate intensity in 60.8% of cases. Insomnia and/or lack of sleep was the most common trigger (73.7%) followed by stress and fatigue in 71% of cases. Migraine caused severe disability in 15.9% of migraineurs. Conclusion: There was a high prevalence of migraine among medical students in Burkina Faso. Stress and irregular sleep were the most common triggers factors. Key words: prevalence, impact, migraine, medical student, Burkina Faso